Interpretation of Dear Me Beauty Product Rebranding: Twitter Users Analysis - Lambok Hermanto Sihombing (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2021)
This study aimed to discuss the way Dear Me Beauty was rebranding their brand by launching new products after they have a brand crisis. The data of this research was obtained from the comment of a Twitter user. This study used the encoding decoding theory from Stuart Hall. The findings of this study was the response from Twitter users was positive, implying that Dear Me Beauty's rebranding was successful. The researchers discovered that the messages from Dear Me Beauty conveyed through their newest product could be well interpreted and accepted by the public.